Carotid endarterectomy has significantly lower risk in the last two decades - Should the guidelines now be updated - Halliday, A; Radak, D; de Waard, D; Tanskovic, S; Neskovic, M (Edizione Minerva Medica, 2017)
Carotid endarterectomy (CEA) carries a significant risk of procedural stroke and death Guidelines recommend keeping this risk below 6% and below 3% for symptomatic and asymptomatic patients respectively. After analysing our Institute’s CEA results during the past 25 years, we found the rate of postoperative complications was now well below Guideline thresholds. Accordingly, we studied temporal changes in procedural risks in randomized controlled trials (RCTs) and in large observational studies in order to compare these against Guidelines. We found a clear temporal trend towards improving procedural outcomes, which can be explained by improvements in medical therapy, more appropriate timing of CEA, the use of local anaesthesia and the use of peroperative cerebral monitoring as well as improving surgical techniques. An update of current guidelines should now be undertaken, since our findings are not unique and are supported by other studies in this review.